Comparative analysis of objective and subjective outcomes of two different intraocular lenses: trifocal and extended range of vision. Issue 1 (14th October 2020) - Pedrotti, Emilio; Carones, Francesco; Talli, Pietro; Bonacci, Erika; Selvi, Federico; Galzignato, Alice; Besutti, Andrea; De Gregorio, Alessandra; Marchini, Giorgio
Abstract : Objective: To evaluate objective and subjective outcomes after bilateral implantation of two different multifocal intraocular lenses, which correct pseudophakic presbyopia in an adequate and homogeneous population court. Methods and analysis: Fifty patients were evaluated at 3 months after bilateral implantation, at the Eye Clinic of University of Verona and at the Carones Ophthalmology Center Milano, as follows: Tecnis Symfony (25 patients), Alcon PanOptix (25 patients). Main outcomes were uncorrected and best-corrected distance visual acuity (UDVA and BCVA) at 4 m, 60 cm (best distance corrected intermediate visual acuity (BDCIVA) and uncorrected intermediate visual acuity), 40 cm (best distance corrected near visual acuity (BDCNVA) and uncorrected near visual acuity (UNVA)), objective refractive outcome, defocus curve, contrast sensitivity (Modulation Transfer Function (MTF) cut-off), optical quality (Strehl ratio), aberrometry (root mean square RMS 4 mm), subjective quality of life (National Eye Institute Refractive Error Quality of Life score (NEI-RQL-42 score) test). Results: Symfony and PanOptix showed BCVA and UDVA comparable results. Symfony presented significant better outcomes at BDCIVA (p=0.001), while PanOptix showed better performances at BDCNVA and UNVA (p=0.01). Symfony achieved better results in RMS 4 mm (p=0.024) and in MTF cut-off (p=0.041). In the questionnaire NEI-RQL-42, PanOptix presented better scores in 'near vision' and 'spectacles independence', whereas Symfony in 'symptoms' and 'clarity of vision'. Conclusion: Both intraocular lenses are valid options to avoid pseudophakic presbyopia, even though they present different features which make them unique. Symfony allows patients to achieve a better objective and subjective quality of vision and contrast sensitivity; PanOptix provides better outcomes in near vision and spectacles independence requirements.